Physical Activity, Boredom and Fear of COVID-19 Among Adolescents in Germany - Bösselmann, Vincent; Amatriain-Fernández, Sandra; Gronwald, Thomas; Murillo-Rodríguez, Eric; Machado, Sergio; Budde, Henning (Frontiers in Psychology, 2021)
Background: The effectiveness of physical activity (PA) as an intervention against anxiety disorders and depression is undeniable in clinical psychology. Therefore, the question arose whether these effects also occur when a fear stimulus, like the COVID-19 pandemic, affects otherwise healthy adolescents. Boredom is closely linked to symptoms of fear and anxiety, but the connection between PA, boredom and fear is partly unclear. Methods: A cross-sectional online study was conducted that involved 122 students. Participants were 13-19 years old (Mage = 15,83, SD = 1,73). The survey was available online from April 27th to May 3rd, 2020. At this time, schools in Germany had already been closed for six weeks. A self-report questionnaire was used to measure physical activity, boredom and fear of COVID-19. A multiple linear regression model was conducted. Results: The reported fear of COVID-19 significantly correlates with total PA, quantity of strenuous PA, and boredom. Furthermore, a significant regression equation was found. The variables boredom, PA, and age contribute significantly to predicting the fear of COVID-19 (R2 = .127, F (3,118) = 6,876, p <.000), among adolescents. Conclusion: Our results indicate that there is an association between PA, boredom and the quarantine experience of adolescents. Students who were physically more active, especially with strenuous intensity, did not feel bored and showed less fear of COVID-19.